Effect of supplementation of Aloe vera extracts in cold storage media and cryopreservation of domestic cat epididymal spermatozoa - Barbosa, Brenna de Sousa (Anim Reprod, 2020)
This study evaluated the effect of the extract of Aloe vera at concentrations of 10% and 20% on the cryopreservation of sperm from the epididymis of domestic cats. Epididymal spermatozoa were recovered using the flotation technique and used in the treatments: control (TRIS-egg yolk at 20%), T10% (TRIS plus 10% of A. vera extract), and T20% (TRIS plus 20% of A. vera extract). The spermatozoa were subjected to 4ºC for 60 minutes, followed by 20 minutes in nitrogen vapors, and stored in a cryogenic cylinder. The samples were thawed at 37°C for 30 seconds. The sperm motility decreased (P<0.05) after thawing in the three treatments. Only the spermatozoa in the control treatment maintained post-thawing vigor. The viability of spermatozoa decreased in the treatments with A. vera (P<0.05). According to the hypoosmotic test, all treatments maintained the sperm membrane functionality (P>0.05) during freezing; however, after thawing, it decreased (P<0.05) in the T10% and T20% treatments. The morphology and chromatin condensation of spermatozoa did not differ, regardless of the treatments and time of evaluation (P>0.05). The effect of the crude A. vera extract was not satisfactory on the cryopreservation of epididymal spermatozoa of domestic cats after thawing; although the motility of spermatozoa was similar to that found with the use of egg yolk, and it presented maintenance of the chromatin integrity. However, it is necessary to understand the action of the substances present in A. vera with the feline spermatozoa, well as the standardization and adjustment of physicochemical characteristics aiming at the future application of the vegetal extract.